Aspects of Anxiety Regarding Career Decision Making in the Future of High School Students - Nurbaiti, Nurbaiti; Lasari, Desy Murni; An-Nabawi, Muhammad Munir (Medan State University, 2023)
The purpose of this study was to determine the understanding and anxiety aspects of SMA Negeri 1 Lhoksukon students about making future career decisions. This type of research is descriptive research. In this study the authors used class XI student informants at SMA Negeri 1 Lhoksukon, North Aceh Regency, as many as 125 students. Given that there were too many informants, namely 125 students, the researchers took informants representing classes XI-1, XI-2, XI-3 and XI-4 per class of one student, so the informants were 4 students. The data collection techniques are observation, interviews and documentation. The result of the first research is the understanding of SMA Negeri 1 Lhoksukon students about making career decisions in the future where students in making career decisions are the process of determining student choices about their careers. The problem is, in fact, there are students who are able to choose a path for their career decisions, and there are also students who are unable to choose a path for their career decisions. In making career decisions there are four processes, namely exploration, crystallization, selection and clarification. The two aspects of anxiety that occur in students when making decisions about future careers for SMA Negeri 1 Lhoksukon students include cognitive aspects, motor aspects, somatic aspects and affective aspects.